2022
DOI: 10.2196/33282
|View full text |Cite
|
Sign up to set email alerts
|

An Exploratory Digital Board Game Approach to the Review and Reinforcement of Complex Medical Subjects Like Anatomical Education: Cross-sectional and Mixed Methods Study

Abstract: Background Serious games have the potential to resolve educational problems faced by medical students, such as insufficient rehearsal due to boredom and lack of motivation. However, serious games’ relatively novel concepts in science and many genres of games that are common in recreation remain underresearched in the literature. Board games are one such genre that, despite their potential, affordability, and flexibility, are rarely designed for medical students, and little is known about student pe… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
31
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 16 publications
(31 citation statements)
references
References 72 publications
(133 reference statements)
0
31
0
Order By: Relevance
“…A review of the available literature has revealed evidence supporting the use of game-based learning in human anatomical education in either a non-computer-or computer-based format, [34][35][36][37][38][39] and including a board game format. [40][41][42][43] However, no educational board game designed for learning orofacial spaces has yet been created, especially to investigate the impact of competition and collaboration on student learning. As such, this research aimed to develop a board game for the teaching and learning of orofacial spaces to undergraduate dental students and to evaluate its implementation on whether a competitive or collaborative approach would be more effective.…”
Section: Introductionmentioning
confidence: 99%
“…A review of the available literature has revealed evidence supporting the use of game-based learning in human anatomical education in either a non-computer-or computer-based format, [34][35][36][37][38][39] and including a board game format. [40][41][42][43] However, no educational board game designed for learning orofacial spaces has yet been created, especially to investigate the impact of competition and collaboration on student learning. As such, this research aimed to develop a board game for the teaching and learning of orofacial spaces to undergraduate dental students and to evaluate its implementation on whether a competitive or collaborative approach would be more effective.…”
Section: Introductionmentioning
confidence: 99%
“…It also showed that the games increased their learning management skills, retention ability of the information learnt, attentiveness and motivation in the laboratory sessions compared to conventional teaching methods (36). Game based learning was also suitable as a rehearsal tool that increased the value of the traditional teaching and learning method (33).…”
Section: Discussionmentioning
confidence: 94%
“…Game-based learning methods significantly affect the student's attitude towards the taught subject (31). Game-based learning stimulates excitement (31), develops more engagement from the student (32,33) and increases study motivation among students and increases their focus on the concept being taught in the class (34)(35)(36). Study by Barros et al (2022) showed that game-based learning such as Kahoot!…”
Section: Discussionmentioning
confidence: 99%
“…Some of these changes are in response to new emerging pedagogical approaches such as moves to a blended learning construct (Pereira et al, 2007; Green & Whitburn, 2016; Khalil et al, 2018), integrated curricula (Evans & Watt, 2005; Klement et al, 2011, 2017), an emphasis on interprofessional learning (Hamilton et al, 2008; Herrmann et al, 2015; Smith et al, 2015) and near‐peer teaching (Evans & Cuffe, 2009; Morris et al, 2018; Harrison et al, 2019). The rise of digital innovations has enabled virtual dissection (Darras et al, 2020; Wainman et al, 2021; Duraes et al, 2022), three‐dimensional (3D) printing (McMenamin et al, 2014; Smith et al 2018; Ye et al, 2020), ultrasound (Swamy & Searle, 2012; Smith & Barfoot, 2021; Lufler et al, 2022), gamification (Ang et al, 2018; Rudolphi‐Solero et al, 2022; Tan et al, 2022) as well as virtual and augmented reality (Moro et al, 2017; Uruthiralingam & Rea, 2020; Zhao et al, 2020; Jiang et al, 2022) to become common features in many programs. Technology has also started to disrupt the way in which students are assessed with interactive e‐assessments being increasingly utilized (Elzainy et al, 2020; Chakrabarti, 2020; Bogomolova et al, 2021).…”
Section: Evolving Anatomical Educationmentioning
confidence: 99%